CUSTOMER PERCEPTIONS ABOUT GREEN MARKETING IN â€œTHE BODY SHOPâ€ MANADO - Polii, Stephani M.; Tielung, James D. D.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
In the present world, people are more conscious about their safety of life and want everything would be environment friendly and making the green world. In an effort to restore the environment, various innovations have emerged the market. Companies are starting to apply the green marketing concept, from product manufacturing to promotion. This study aims to find out the opinions of customers who buy products in stores that have applied environmentally friendly concepts based on green companyâ€™s 4Ps (product, price, place, promotion). The number of respondents is 10 people. A qualitative approach is taken as a research method and purposive sampling done with primary data of 10 consumers. The findings show that customers feel comfortable with green products and the benefits offered by the company. It was also found that information and knowledge about green products were plenary and only a few were involved in the environmentally friendly campaigns made by the company.Â Keywords: green marketing, customer perceptions, qualitative research.